Prolonged hypoxia delays aging and preserves functionality of human amniotic fluid stem cells. (October 2020) - Casciaro, Francesca; Borghesan, Michela; Beretti, Francesca; Zavatti, Manuela; Bertucci, Emma; Follo, Matilde Yung; Maraldi, Tullia; Demaria, Marco
Highlights: Human amniotic fluid stem cells (hAFSCs) are an emerging tool in regenerative medicine. Expansion of hAFSCs ex vivo is limited by various factors. Low oxygen culture conditions extend stemness and proliferative features of hAFSCs. Low oxygen culture conditions delay the onset of stem cells aging. Abstract: Human amniotic fluid stem cells (hAFSCs) are an emerging tool in regenerative medicine because they have the ability to differentiate into various lineages and efficiently improve tissue regeneration with no risk of tumorigenesis. Although hAFSCs are easily isolated from the amniotic fluid, their expansion ex vivo is limited by a quick exhaustion which impairs replicative potential and differentiation capacity. In this study, we evaluate various aging features of hAFSCs cultured at different oxygen concentrations. We show that low oxygen (1% O2 ) extends stemness and proliferative features, and delays induction of senescence-associated markers. Hypoxic hAFSCs activate a metabolic shift and increase resistance to pro-apoptotic stimuli. Moreover, we observe that cells at low oxygen remain capable of osteogenesis for prolonged periods of time, suggesting a more youthful phenotype. Together, these data demonstrate that low oxygen concentrations might improve the generation of functional hAFSCs for therapeutic use by delaying the onset of cellular aging.